Resource Financed Infrastructure : A Discussion on a New Form of Infrastructure Financing - Halland, Havard; Beardsworth, John; Land, Bryan; Schmidt, James (Washington, DC: World Bank, 2014)
This report, consisting of a study prepared by global project finance specialists Hunton and Williams LLP and comments from six internationally reputed economists and policy makers, provides an analytical discussion of resource financed infrastructure (RFI) contracting from a project finance perspective. The report is meant as a forum for in-depth discussion and as a basis for further research into RFI's role, risks, and potential, without any intention to present a World Bank, supported view on RFI contracting. It is motivated by the conviction that if countries are to continue to either seeks RFI or receive unsolicited RFI proposals, there is an onus on public officials to discern bad deals from good, to judge unavoidable trade-offs, and to act accordingly. The report aims to provide a basis for developing insights on how RFI deals can be made subject to the same degree of public policy scrutiny as any other instrument through which a government of a low or lower-middle-income country might seek to mobilize development finance. The report also feeds into the global mainstreaming of 'open contracting,' providing citizens with the means to engage with governments and other stakeholders on how nonrenewable resources are best managed for the public benefit. In the case of RFI, there is a very direct link made between the value of resources in the ground and the development of (infrastructure) benefits. It should not be a surprise, therefore, that the revised Extractive Industries Transparency Initiative (EITI) Standard, adopted in May 2013, addresses extractive transactions with an infrastructure component, including RFI.